PENEGAKAN HUKUM TINDAK PIDANA PEMBUANGAN LIMBAH BERBAHAYA DAN BERACUN KE ALIRAN SUNGAI MENURUT UNDANG – UNDANG NOMOR 32 TAHUN 2009 - Hardiansyah Lubis,Yeltriana (YAPEKAM, 2024)
This study aims to relate to legal regulations regarding the crime of dumping hazardous and toxic waste into rivers, what factors cause the crime of dumping hazardous and toxic waste into rivers, what obstacles are faced by law enforcement officers in preventing and overcoming the crime of dumping hazardous and toxic waste into rivers. The data collection method in this study was carried out by literature study, which is a way of collecting data by searching and reviewing library materials (literature, research results, scientific magazines, scientific bulletins, scientific journals, etc.). Legal materials were collected through inventory procedures and identification of laws and regulations, as well as classification and systematization of legal materials according to research problems. Therefore, the data collection technique used in this study was literature study. Literature study was carried out by reading, reviewing, taking notes, making reviews of library materials that are related to Law Enforcement for Perpetrators of the Crime of Dumping Hazardous and Toxic Waste into Rivers. Provisions related to waste management and hazardous and toxic materials have been emphasized in Chapter VII Article 58 to Article 61 of Law No. 32 of 2009 concerning Environmental Protection and Management, Government Regulation PP Number 18 of 1999 as amended by PP Number 85 of 1999, starting in Article 40 to Article 46. Meanwhile, regarding the control of the impact of hazardous and toxic waste (LB3) through the Regulation of the Minister of State for the Environment Number 18 of 2009 concerning Procedures for Licensing the Management of Hazardous and Toxic Waste.